Capturing the subject-specific quality of mathematics instruction: How do expert judgments relate to students’ assessments of the quality of their own learning and understanding? - Pauli, Christine; Lipowsky, Frank; Reusser, Kurt (ZDM, 2024)
Based on an opportunity-use model of instructional quality, this study investigates the extent to which subject-specific instructional quality rated by experts is reflected in students’ assessments of their own learning and understanding, and how students’ perceptions predict their achievement. The analyses used data from a German-Swiss sample of 36 classes with around 900 lower secondary students, obtained as part of the so-called “Pythagoras study” in the school year 2002/2003. The teachers were instructed to introduce the Pythagorean theorem in three lessons, which were videotaped. Using the videos, the experts assessed the instruction quality with respect to the goal of promoting a deep understanding of the theorem. The students completed the questionnaires assessing their understanding of the content, their learning process, and the general comprehension orientation of the teacher. The results showed significant and moderate correlations on the class level between expert-rated subject-specific teaching quality and students’ perceptions of their own learning and understanding, as well as of the teacher’s general comprehension orientation. Multilevel models revealed that subject-specific expert ratings are reflected in individual students’ perceptions of their own learning and understanding. Student perceptions were also associated with achievement gains. The results suggest that the assessment of quality by students and experts is more closely linked if a distinction is made between the quality of the learning opportunities offered and their use and if subject-specific criteria are used instead of generic criteria. This study contributes to a more nuanced understanding of the validity of student perspective in assessing instructional quality.